Utilizing Canva Media to Improve High School Students' Creativity - Nitya Tutayomi; Qurrota A’yun; Suparmi (Mazidah: Journal Of Educational Research, 2026)
Creativity is an innate ability in every individual, not something that is acquired from external sources. For the material presentation system, the use of technology is very important as a means to design, review, assess development results, and apply learning materials effectively. Technology helps facilitate this process, thereby improving the quality of teaching and learning. This article aims to discuss the use of Canva in increasing the creativity of high school students. The method used is qualitative media, namely a literature review of articles published between 2020 and 2025, using Google Scholar and Publish or Perish to search for relevant articles. The results of the study describe that Canva can play a role in supporting students' creativity to support learning and improve students' skills, supported by a sufficient surrounding environment. Areas that do not yet have adequate technological facilities are expected to be a concern for the government in providing adequate facilities so that no gaps arise. In conclusion, Canva supports students in increasing their creativity, and there are many aspects that support improvements in learning and social aspects.